2011
DOI: 10.1007/s00586-011-1796-4
|View full text |Cite
|
Sign up to set email alerts
|

Low pressure pain thresholds are associated with, but does not predispose for, low back pain

Abstract: Chronic pain is often associated with hyperalgesia in cross-sectional studies. In the present study, a random cohort of 40-year-old individuals (n = 264) from the general population was assessed for low back pain (LBP) status and pressure pain threshold (PPT), with follow-up assessment 4 and 8 years later. Low PPT at baseline as a potential risk factor for the development of LBP was investigated longitudinally and the association between LBP and hyperalgesia was studied cross-sectionally at baseline and 8-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
48
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 27 publications
6
48
2
2
Order By: Relevance
“…Yet, no association has been found between recently developed low-back pain and PPTs [3]. Thus, it appears that deep-tissue hypersensitivity exists in individuals with long-lasting but not short-term low back pain [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, no association has been found between recently developed low-back pain and PPTs [3]. Thus, it appears that deep-tissue hypersensitivity exists in individuals with long-lasting but not short-term low back pain [3].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that pain thresholds in a non-painful body area could be affected in pain states [2][3][4][5]. More specifically, it has been found that pressure pain thresholds (PPTs) are lower in the tibialis anterior muscle in patients with chronic low back pain compared to controls [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is uncertain, for example, whether sensory and perceptual changes are present before pain, occur after pain onset, or develop as pain persists (Hübscher et al 2014;O'Neill et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…low back pain (LBP) [1][2][3][4][5]. However standardized assessment of pain sensitivity and central modulation of pain sensitivity is probably used only rarely in clinical practice.…”
Section: Introductionmentioning
confidence: 99%